Community structure and estimation of aboveground biomass and carbon stock of beach forest in Barangay Mambatad, Miagao, Iloilo Philippines - Ledesma, Dencee Jean T.
In general, forests help mitigate climate change by acting as carbon sinks in addition to the numerous goods and services they provide. While people are too familiar with forests on hills and mountains including the mangroves, the beach forest is almost unknown to many. Beach forest were the first to be removed from coastal areas without knowing that they provide ample benefits to humanity. They act as bioshields from natural calamities such as storm surges, tsunamis, and tidal wave actions. Unfortunately, there is little or scanty information about these forests. Thus, the need for this study. This study aimed to assess the community structure and estimate the carbon stock and aboveground biomass of beach forest in Barangay Mambatad, Miago, Iloilo, Philippines. Specifically, it aimed to: a) Identify the beach forest species present in the area; b) Describe the community structure in terms of: species composition, diameter at breast height and stand height, stand basal area, importance value, index of biodiversity, species richness and evenness; c) Determine aboveground biomass and carbon stock; and d) Determine whether there is a relationship between beach forest species diversity index and carbon stock. Transect line plot method was used with three transects established for a total of seven plots. Results showed that a total of 46 beach forest species was recorded belonging to 23 families. The total SBA was 44.32 m2ha-1. Cocos nucifera recorded the highest importance value (IV = 66.04). However, the beach forest in Brgy. Mambatad showed a low diversity and evenness index (H?=0.45; J?=0.75) that could be attributed to earlier conversion of the site to residential and recreational facilities. Additionally, the calculated biomass and carbon stock for the site were 327.5 t/ha and 105.6 t/ha, respectively. This study has shown that despite the highly disturbed state of the beach forests, a substantial amount of carbon is still stored in the remaining forests. Thus, protection, preservation and conservation measure should be enacted for better management of this valuable but fragile ecosystem.